Seasonal course of anthropogenic air pollution and surface ozone concentrations in the cities of Belarus - Liudchik, Alexander; Akimov, Aleksandr (Journal of the Belarusian State University. Ecology, 2023)
Based on the data of the National Environmental Monitoring System, the levels of anthropogenic air pollution and surface ozone in the regional cities of Belarus and the Berezinsky Biosphere Reserve are analyzed. The features of the diurnal course of pollution concentrations are discussed. Monthly average values of concentrations in different years for each observation site were calculated and their long-term averages for each observation site and average monthly pollution levels for cities with several observation sites were determined. Changes in air pollution levels over the years and differences in pollution levels in individual cities are analyzed. The observed differences is due not only to different sources of air pollution and their intensity, but also to differences in meteorological conditions. General conclusions can be drawn regarding the seasonal course of pollution concentrations: almost all of them are maximum in February, then fall towards the summer and increase in the autumn period until the following February. Only with volatile organic compounds, no clear recurring seasonal dependence was found at all observation points. The general decrease in pollution concentrations in summer is explained by a decrease in the vertical stability of the atmosphere, intensification of its vertical mixing, and dilution of pollution concentrations in the surface air layer. The revealed decrease in concentrations of anthropogenic pollution in cities in recent years also requires a more detailed analysis to determine its causes. Two possible reasons are a reduction in emissions from industrial enterprises and, after all, a changing climate, leading to an intensification of urban air purification. According to the results of the study, the cleanest air is in the Berezinsky Reserve. However, in Brest, Mogilev and Grodno, the concentrations of ground-level ozone in the spring-summer period are higher than in the Reserve, despite significantly higher concentrations of anthropogenic pollution in cities compared to the Reserve. The explanation should be sought in the difference in weather conditions and the transboundary transport of pollution and ozone. The concentrations of carbon monoxide vary slightly in individual cities, the highest – in Gomel, the lowest – in Minsk. As for volatile organic compounds, the highest are in Minsk, the lowest are in Gomel. And in terms of nitrogen oxide pollution, both of these cities are leaders among the regional centers of the Republic.
Keywords: surface ozone; meteorological conditions; anthropogenic air pollution